From the Internet to the everyday: An exploration of visual representations of peace - Prinzing, Isabel; Brantner, Cornelia; Lobinger, Katharina (AoIR Selected Papers of Internet Research, 2026)
While extensive research has explored the role of images in war, studies on peace imagery remain limited. This gap is significant given images’ ability to shape public perception, evoke emotions, and convey immediacy, which is often absent in text. Moreover, dominant visual narratives tend to frame peace within a binary war-peace paradigm, at times overlooking the diverse, coexisting forms of peace emphasized in contemporary peace research.This study addresses these gaps by examining peace imagery through a dual approach: analyzing images selected by over 200 peacebuilding experts and conducting a systematic Google Images search using 15 peace-related keywords.Using image-type analysis, the study categorizes and interprets recurring motifs, revealing distinct differences between participant-selected images and those retrieved from online searches. While dominant online peace imagery often features symbols, text-based visuals, and staged representations, expert-selected images highlight more nuanced portrayals of everyday peace, emphasizing local, lived experiences. These findings underscore the need to move beyond simplistic peace symbols and incorporate diverse, grassroots-driven visual narratives.By bridging expert surveys with digital methodologies, this study enhances our understanding of peace representation and its implications for global peace communication. The results highlight the role of the Internet in shaping dominant peace imagery while advocating for a more inclusive, locally grounded visual discourse. This research ultimately contributes to expanding visual peace studies and integrating diverse perspectives into broader peacebuilding efforts.